Artificial Intelligence (AI): Perception and Utilization of AI Technologies in Educational Assessment in Nigerian Universities - Ibrahim, Abdul-Wahab; Taura, Ali Abdullahi; Iliyasu, Abdullahi; Shogbesan, Yusuf Olayinka; Lukman, Shehu Adaramaja (Edukasiana: Jurnal Inovasi Pendidikan, 2024)
The ubiquity of Artificial Intelligence (AI) has generated different perceptions and views regarding its usefulness in conducting educational assessment in Nigerian universities. This study determined whether academic integrity and innovative assessment concerns affect how university teachers utilize diverse AI tools in educational assessment. It also investigated if university teachers’ perception of using AI tools is likely to be associated with their tendency to personalize AI use at universities in the country. The study adopted inferential research design. 3,083 university teachers comprised the population in the study, out of which the sample of 322 participants who are professors, associate professors, and senior lecturers from government and privately-owned universities, were randomly selected for the study. The instrument was a 4-point scale questionnaire titled: “University Teachers’ Perception and Utilization of AI Questionnaire (UTPUAIQ).” The data were analyzed using independent t-test, Pearson Product Moment Correlation and Chi-Square statistics, as percentile analysis was explored using simple percentage statistical procedure. The results revealed that academic integrity concerns have an influence on how university teachers perceive AI use in assessment; that perception for innovative assessment concerns at university significantly affects how university teachers utilize diverse AI tools in educational assessment; and that university teachers’ perception of using AI tools is likely to be associated with their tendency to personalize AI use at universities. It was concluded that AI use in educational assessment is in itself not harmful but the potential risks involved must be mitigated as it is deployed for use for students’ assessment at universities in Nigeria. Hence, there is a need to ensure the ethical, inclusive and equitable use of AI in educational assessment at universities in the country.